OP05 The impact of comorbidities on outcome of patients assessed for liver transplantation, waiting list mortality and post liver transplantation survival using the Charlson comorbidity index. (6th September 2011) - Al-Freah, M A B; Dionigi, E; Blackmore, L; Johnston, E; Zubir, A; Foxton, M; Bernal, W; Auzinger, G; Rela, M; Heaton, N D; O'Grady, J G; Heneghan, M A; et al.
Abstract : Introduction: Severity of liver disease determines accurately the outcome of patients on liver transplant (LT) waiting list (WL). Comorbidities are known to affect post-LT outcomes but their effect on outcome of transplant assessment (TA) or WL mortality have not been fully explored in previous studies. Aim: To study the impact of comorbidities on TA, WL mortality and post LT survival. Method: Retrospective study of all patients assessed for LT at our centre between 1 January 2000 and 31 December 2007 (n=1484). Patients with acute liver failure (175), amyloid (43), those assessed for re-LT (149) and 24 with incomplete information were also excluded. Nine comorbidities (Charlson Comorbidity Index - CCI) were prospectively defined according to Volk et al ( Liver Transplant 2007;13 :1515–20). Kaplan–Meier analysis was performed to determine impact of comorbidity on outcome. Cox regression hazard analysis was used to determine predictors of outcome and presented as (OR, 95% CI, p value). Results: We analysed 1093 patients. Median age was 54 years (17–84), 67.5% were men (738). There were 192 (17.6%) patients with hepatocellular carcinoma (HCC). Patients with ≥1 comorbidity were 499 (46.6%) with most common comorbidities being diabetes (23.2%) and renal dysfunction (12.1%). Of 1093 assessed patients, 826 (75.6%) were listed. Patients with ≥1 comorbidity had significantly decreased LT free survival (log rank =33.586, p<0.001). Multivariate analysis showed CCI (1.79, 1.52 to 2.11, p<0.001), age (1.03, 1.00 to 1.05, p=0.035), Na (0.93, 0.89 to 0.97, p=0.001), MELD (1.10, 1.06 to 1.14, p<0.001) as being predictive. Of those listed for LT (826), 600 (72.6%) were transplanted, 161 (19.5%) died on WL and 65 (7.9%) were delisted. Listed patients with ≥1 comorbidity had significantly decreased LT free survival (log rank =9.045, p=0.003). Multivariate analysis showed CCI (1.79, 1.52 to 2.11, p<0.001), age (1.02, 1.01 to 1.03, p=0.006), pre-LT Hb level (0.87, 0.80 to 0.95, p=0.003), Na (0.96, 0.93 to 0.99, p=0.014) and MELD (1.14, 1.11 to 1.18, p<0.001) were predictors of listing outcome. Transplanted patients with ≥1 comorbidity had significantly decreased post LT survival (Log rank =7.645, p=0.006). Multivariate analysis showed that only CCI (1.36, 1.13 to 1.64, p=0.001) and HCC (1.74, CI 1.21–2.51, p=0.003) were independently associated with post-LT mortality. Similar post LT survival results seen when CCI was divided into 0, 1 and ≥2 comorbidities (Log rank =11.342, p=0.003). Conclusion: We demonstrate that comorbidities significantly impact on the outcome of patients with chronic liver disease at TA, on wait-list and post LT survival. Adding CCI to known liver prognostic models may improve their prediction ability.